TRICHODERMA AS A PROFICIENT BIOCONTROL AGENT FOR PHYTO-PATHOGENIC FUNGI – MECHANISM OF ACTION AND GENETIC ADVANCES (Applied Biological Research, 2024)
Plant disease management presently relies heavily on chemical fungicides.  However, their harmful impact on human and ecosystem, and development of  fungicide-resistant strains has emphasized on biological control as alternative  eco-friendly strategy for disease management and sustainable agriculture.  Trichoderma is a widely used as biocontrol agent against various phyto pathogenic fungi owing to its effective strategies to suppress plant pathogens.  The control phenomenon involves direct mechanisms like mycoparasitism,  secretion of hydrolytic enzymes which degrade the cell walls of pathogenic  fungi, and indirect mechanisms like competition for resources, induction of  plant defense mechanism and antibiosis. Trichoderma’s multifaceted approach  to biological control makes it environment-friendly option for managing plant  diseases. Recent biotechnological approaches have simplified the isolation and  characterization of efficient biocontrol agents, along with the identification of  their genetic by-products. These techniques facilitate the cloning of these  microbes in plants, with aim to bolster their resistance to both biotic and  abiotic stresses. Biotechnological advances have not only reinforced the  symbiotic interaction between microbes and plants but also allowed the  modification of processes through microbial biocontrol agents (MCBAs).  Genome sequencing of MBCAs has provided valuable insights into their  genetic makeup, aiding their characterization. The present comprehensive review provides an insight to the existing and recent molecular advances  utilized to enhance the efficiency of MBCAs in managing plant diseases and  understanding biocontrol mechanisms through various omics technologies.
Keywords: Biological control; genomics; mutagenesis; phytopathogens; proteomics; transcriptomics; Trichoderma